Full Color Luminescent Difluoroboron β−Diketonate PLA-PEG Nanoparticle Imaging Agents - Kerr, Caroline (Biomacromolecules, 2017)
Luminescent difluoroboron β-diketonate poly(lactic acid) (BF(2)bdkPLA) materials serve as biological imaging agents. In this study, dye structures were modified to achieve emission colors that span the visible region with potential for multiplexing applications. Four dyes with varying π−conjugation (phenyl, naphthyl) and donor groups (-OMe, -NMe(2)) were coupled to PLLA-PEG block copolymers (~11 kDa) by a post-polymerization Mitsunobu reaction. The resulting dye-polymer conjugates were fabricated as nanoparticles (~55 nm diameter) to produce nanomaterials with a range of emission colors (420–640 nm). For increased stability, dye-PLLA-PEG conjugates were also blended with dye-free PDLA-PEG to form stereocomplex nanoparticles of smaller size (~45 nm diameter). The decreased dye loading in the stereoblocks blue-shifted the emission, generating a broader range of fluorescence colors (410–620 nm). Tumor accumulation was confirmed in a murine model through biodistribution studies with a red emitting dimethyl amino-substituted dye-polymer analogue. The synthesis, optical properties, oxygen-sensing capabilities, and stability of these block copolymer nanoparticles are presented.